Model Pendidikan Karakter Sekolah Menengah Kejuruan: Studi Kasus di Smk Muhammadiyah 3 Purbalingga - Wibowo, Sareh Siswo Setyo (International Conference of Moslem Society, 2016)
The formation of character is needed by adolescents in this era. It is based with the many phenomena of juvenile delinquency. Characters will not be formed away so it needs an effort should be made of teachers in shaping the character of teenagers. In addition, the authors found the variation of the efforts of teachers holistically so that teenagers will easily formed his character in accordance with the purpose of the character education. The problem of this research is how the character education model Vocational High School who applied in the implementation of the formation of character in SMK Muhammadiyah 3 Purbalingga. The purpose of this study is the author would like to know a clear picture of the implementation of character education model in efforts to form children's character in School SMK Muhammadiyah 3 Purbalingga. This paper discusses the character education model be applicable in the planting of character values ​​to students in Vocational High School Muhammadiyah 3 Purbalingga. This type of research is a field research is descriptive qualitative. Data collection methods used include interviews, observation and documentation. As for analyzing the data obtained, the authors do by collecting all the data, reducing the data, presenting data, and verification of data. Results from this study showed that the model of character education is done to instill character values ​​to learners School SMK Muhammadiyah 3 Purbalingga using reflective models. Use of the character models adhering to the principles of character education and values ​​are developed in accordance with the level of development of learners.